O discurso sobre leitura na esfera escolar e sua relação com o discurso científico - Cardoso, Rosana; Mendonça, Marina Célia [UNESP] (My University, 2010)
In this paper, the discourse about reading skills uttered by teachers and students is analyzed. The analyses are supported by the Bakhtin’s studies concerning the discourse that necessarily consider the meaning affected by the sphere of the activity in which the enunciation occurs. The concrete utterance, in this perspective, has its identity in relation to the social values that constitute the conscience of the author and in the ideologies that materialize in the discourse, which is always marked by the constitutive relation between the other person and me. The results indicate the following conclusions: the common sense discourse about reading appears in the answers of the analyzed teachers, which consider their students like bad readers, these professionals also do not recognize the technology as a source of reading for their students. Thus, reading that interests the students is not acceptable in school. The symbolic violence practiced by school appears at the moment that the teacher does not consider the student’s language and the readings that interest them; it also appears when the teacher prevents their students to have new readings; moreover, reading is always unique as it is neither new, nor unrepeatable, so it the plurality of meanings is impossible.

Neste trabalho, é analisado o discurso sobre as habilidades de leitura enunciado por professores e alunos. A base teórica que sustenta as análises são os estudos bakhtinianos do discurso, que consideram o sentido necessariamente afetado pela esfera de atividade em que ocorre a enunciação. O enunciado concreto, nessa perspectiva, tem sua identidade na relação com os valores sociais que constituem a consciência do autor e nas ideologias que se materializam no discurso, sempre marcado pela relação constitutiva entre o eu e o outro. Os resultados apontam para as seguintes conclusões: o discurso do senso comum sobre leitura aparece nas respostas dos professores analisados, os quais consideram seus alunos maus leitores; esses profissionais também não reconhecem a tecnologia como fonte de leitura para seus alunos. Assim, leitura que interessa aos alunos não é aceita na escola. A violência simbólica praticada pela escola aparece no momento em que o professor desconsidera a linguagem do aluno e as leituras que lhes interessam; também aparece quando o docente impede seus alunos de realizarem novas leituras; ademais, a leitura é sempre única, não há o novo, o irrepetível, o que impossibilita a pluralidade de significações.
The discourse about reading in the scholar´s sphere and its relation with the scientific discourse
Keywords: Discourse analysis; Reading; School; Bakhtinian studies; Discurso científico; Discurso do senso comum; Estudos bakhtinianos